Pengaruh Teori Laissez Faire terhadap Mekanisme Pasar Adam Smith - Rismanika Nurul Utami; Rizky Mohammad Rezy; Wiji Lailatul Maftukhah (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
This research is motivated by the existence of a relationship between Laissez Faire Theory and the free market mechanism. Laissez Faire theory is a leadership style in which the leader gives freedom to his subordinates to carry out their duties freely. Meanwhile, the free market mechanism is a market where sellers and buyers are given the freedom to carry out their trading activities, including determining the equilibrium price. Where in the free market mechanism this occurs without government intervention. Adam Smith wanted freedom to be given to everyone without government interference. The purpose of this study is to analyze the effect of Laissez Faire Theory on the free market mechanism. The method used in this research is descriptive qualitative method and the type of research used is literature, where the data collected is only obtained from written works and several books. The results of the study indicate that individual freedom makes the realization of the free market mechanism. Because of this individual freedom, individuals are free to use resources so as to create an urge to take risks and work hard. Individuals are free to determine the stage of production and the price level in a free market mechanism so as to create a price balance and obtain a profit that can meet needs.